Lithium recovery from geothermal brine – an investigation into the desorption of lithium ions using manganese oxide adsorbents. (21st September 2022) - Herrmann, Laura; Ehrenberg, Helmut; Graczyk-Zajac, Magdalena; Kaymakci, Elif; Kölbel, Thomas; Kölbel, Lena; Tübke, Jens
Abstract : Spinel type lithium manganese oxides (LMOs) are promising adsorption materials for selective recovery of lithium from salty brines. Abstract : Spinel type lithium manganese oxides (LMOs) are promising adsorption materials for selective recovery of lithium from salty brines. In this work a lithium-ion sieve material, H1.6 Mn1.6 O4, derived from Li1.6 Mn1.6 O4, a spinel type LMO, was successfully prepared via hydrothermal synthesis. This lithium-ion sieve, H1.6 Mn1.6 O4, was then used in laboratory tests to adsorb Li + from a generic LiCl solution and geothermal brine from Bruchsal geothermal power plant. Desorption experiments were performed with the following desorption solutions: ammonium peroxydisulfate ((NH4 )2 S2 O8 ), sodium peroxydisulfate (Na2 S2 O8 ), acetic acid (CH3 COOH), sulfuric acid (H2 SO4 ), carbonic acid (H2 CO3 ), ascorbic (C6 H8 O6 ) and hydrochloric acid (HCl). The results showed that C6 H8 O6 led to adsorbent destruction and only small amount of lithium was desorbed with H2 CO3 . CH3 COOH and (NH4 )2 S2 O8 showed the best desorption performance with high lithium recovery and low Mn dissolution. The kinetic experiments indicate that more than 90% of equilibrium was reached after 4 hours. A decline in the adsorption/desorption capacity was measured for all desorption agents after eight cycles in the long-term experiments. These long-term tests revealed that higher lithium recovery in desorption with HCl and CH3 COOH was achieved compared to (NH4 )2 S2 O8 . On the other hand, the use of CH3 COOH and (NH4 )2 S2 O8 seems to be advantageous to HCl because of lower Mn dissolution. According to the XRD results, the spinel structure of the treated adsorbents was preserved, but a weakening of the peak intensity was observed. Analyzing the adsorbent composition after eight cycles, an accumulation of competing ions was observed. This was especially remarkable when acetic acid was used.